Tingkat Pengenalan Masyarakat Terhadap Jenis Tumbuhan Obat Di Kecamatan Peusangan Selatan Kabupaten Bireun - Saudah Saudah; Saida Rasnovi; Zumaidar Zumaidar (Jurnal Serambi Engineering, 2019)
The level of community recognition of medicinal plants in the Peusangan Selatan district of Bireun Regency is still low and has not been scientifically validated. This study aims to know about the community knowledge in used plant as traditional medicine. The method used in data collection is Participatory Rural Appraisal (PRA) and observation techniques. Inter-views were conducted semi-structurally based on a number of questionnaires. Collection of plant specimens is taken di-rectly from the location of growth assisted by the respondent or community. Primary data obtained from interviews were tabulated and  then  analyzed descriptively and presented In tables and figures. The results of the study obtained 23 species of medicinal plants that were grouped into 13 family. The most of plant used are from the  ingiberaceae and Apiaceae. Percentage of plant species that are often used based on community knowledge are Curcuma longa, Carica papaya, Jatropa curcas, Lowsoniaenermis.